Evaluation of bacteriophage therapy of Aeromonas hydrophila infection in a freshwater fish, Pangasius buchanani - Kumari, Ritu; Yadav, Ragini; Kumar, Deepak; Chaube, Radha; Nath, Gopal (Frontiers in Aquaculture, 2023)
Introduction: The present study aimed to optimize the doses and schedule of specific bacteriophage cocktails in freshwater fish infections as prophylactic and therapeutic measures. Methods: The three most active phages against Aeromonas hydrophila (φAHBHU12, φAHBHU16, and φAHBHU19) were characterized phenotypically and genotypically. Intramuscular and oral routes were used for the lethal dose 100 (LD100) of A. hydrophila and were determined in Pangasius buchanani. The phage therapy was given simultaneously and after 6, 12 and 24 hours of bacterial challenge through intramuscular and oral routes. Results: The prophylactic and early phage administration could save the fish. Further, the dose of intramuscular 1.0×104 PFU/fish and oral 1.0×106 PFUmL-1 of the phage cocktail was optimal. Discussion: The efficacy of bacteriophage therapy as preventive or curative measures practical when administered simultaneously or early hours of A. hydrophila infection in aquaculture systems. Phage-based approaches may be used as an alternative to antibiotics in aquaculture to reduce antibiotic use as a part of the One Health approach.